Problems associated with plate bonding methods of strengthening reinforced concrete beams - Jumaat, Mohd Zamin; Alam, M.A. (Journal of Applied Sciences Research, 2006)
This paper reviews works on problems associated with plate bonding or plating methods of strengthening reinforced concrete beams. Every structural element should be designed for a particular type of loading. However many civil structural elements, like reinforced concrete beams are often required to be upgradedor strengthened due to increased load requirements. Strengthening is becoming both environmentally and economically more preferable than replacement. Different types of materials and methods such as sprayed concrete, ferrocement, steel plate and fibre reinforced polymer (FRP) are available for strengthening existing reinforced concrete beams. However, plating methods of steel plate and FRP laminate are the most popular methods amongst the other methods. In this paper, strengthening of plating methods by using steel plate and fibre reinforced polymer (FRP), and the methods of applying these materials are reported. The advantages and disadvantages of these materials are also reported. Furthermore the problems associated with this plating methods by using two these two materials (steel and FRP) are briefly discussed in this paper.